2003
DOI: 10.1046/j.1537-2995.2003.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal blood volume of donors during automated intermittent‐flow plasmapheresis and its relevance to the prevention of circulatory reactions

Abstract: Application of an arbitrary threshold of 15 percent of the donors' blood volume not to be exceeded during hemapheresis procedures is expected to lead to an unjustified deferral rate in plasmapheresis donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…Intermittent‐flow plasmapheresis (IFP) often involves a high extracorporeal blood volume (ECV) of the donor during the procedure 1,2 with the concomitant risk of circulatory reactions. It has been shown that the ECV can exceed 20 percent of the donor’s blood volume (BV) during this procedure, especially in women, 3 even if current donor suitability criteria 4 are applied. This is because BV restoration through transcapillary refill cannot compensate for the fluid loss occurring during IFP 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent‐flow plasmapheresis (IFP) often involves a high extracorporeal blood volume (ECV) of the donor during the procedure 1,2 with the concomitant risk of circulatory reactions. It has been shown that the ECV can exceed 20 percent of the donor’s blood volume (BV) during this procedure, especially in women, 3 even if current donor suitability criteria 4 are applied. This is because BV restoration through transcapillary refill cannot compensate for the fluid loss occurring during IFP 3 .…”
mentioning
confidence: 99%
“…It has been shown that the ECV can exceed 20 percent of the donor’s blood volume (BV) during this procedure, especially in women, 3 even if current donor suitability criteria 4 are applied. This is because BV restoration through transcapillary refill cannot compensate for the fluid loss occurring during IFP 3 . In contrast, circulatory reactions do not occur more frequently during IFP than in whole‐blood donation 5,6 .…”
mentioning
confidence: 99%
“…Thus, ECVmax values of more than 15% are not generally accepted by regulatory authorities. However, we have already shown in a previous study that the ‘15% limit’ is frequently violated in plasmapheresis programmes [2], without leading to an increased incidence of hypovolaemic donor reactions [3], and we found that these criteria are unsuitable for the prediction or the prevention of such reactions [4]. These findings apply to ECVmax values up to approximately 20%.…”
mentioning
confidence: 68%
“…Therefore as shown in the analysis, adverse reactions of blood donation are a chain of reactions, which starts gradually with a banal vaso-vagal stimulus and then evolves inexorably into syncope, if not adequately treated. [7][8][9][10][11][12] An analysis between age of the donor and adverse reaction was made, 54% of the adverse reactions were seen in the donors of age group 18-28years. 8% of the reactions were seen in 28-38 years age group, 25.7% of reactions were seen in the age group of 38-48 years.28 % of donor reactions were seen in the age group of 48-58 years.…”
Section: Chart 9: Percentage Of Reactions On Y-axis Time Interval Onmentioning
confidence: 99%